Political Marginalization of Pakistani Transgender Community: A Case Study of District Bahawalpur - Akhtar, Shakil; Sadiq, Rabia; Nailakanwal; Mumtaz, Junaid; Bukhari, Syed Adeel Ahmad (The journal of contemporary issues in business and government, 2021)
If all groups of any society are not treated equally and given with opportunities to work for their betterment then that society cannot relish the zenith of prosperity and progress. Same goes with political opportunities. Equal political participation is the beauty of any civilized and democratic society. From the time of Greek political philosophers, it has been seen that a polity is respected and even raised in status if the political participation and awareness of masses is high. Correspondingly, in the 21st century a country with stable politics, democracy and highest equal political opportunities is considered to be developed. Especially the political rights and role of minorities-like women, transgender and religious minorities has great significance in political development of a society. Sad to say, Pakistan lacks political participation of minorities. Political development of Pakistan is at its lowest. This study focuses on the political participation of transgender community in the district Bahawalpur Punjab, Pakistan. Semi-structured interviews had been conducted. The study finds out that political participation of transgender community can be surged if they are educated and reserved seats are being fixed for them. The study recommends that government should make sure to provide educational facilities to transgender community.